LH, FSH, estradiol and progesterone levels after discontinuation of hormonal contraception - Balogh, A; Ditrói, F; Lampé, L G (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1981)
A study was initiated by the Department of Obstetrics and Gynecology at the University Medical School in Debrecen, Hungary in 1978 for the purpose of analyzing some endocrine parameters of the early postcontraceptive period. Blood levels of luteinizing hormone (LH), follicle stimulating hormone (FSH), estradiol, and progesterone levels were studied by specific radioimmunoassay methods in 24 healthy women, ranging in age between 25-36 years, immediately after discontinuing a 4-10 years' use of a combined oral contraceptive (OC) drug. The blood collection period started in the 2nd half of the last pill cycle and continued throughout the 1st, then the 3rd postpill cycles. Thus the collected material allowed study of the diurnal changes of these hormone levels and made it possible to compare a period still on the pill, the 1st month after discontinuing of taking the pill until the 1st spontaneous menstruation, and the 3rd postpill cycle in the same women. The results indicated ovulatory changes in the hormone levels studied in 17 out of 24 women in the 1st cycles and 21 in the 3rd cycles. The rest of the cycles proved anovulatory. The 1st spontaneous cycle was significantly longer than both the control cycles and the 3rd postpill cycles. Statistical analysis showed that basal levels and height of the midcycle LH peak, and basal FSH levels were found to be lower in the 1st versus 3rd postpill ovulatory cycles. Luteal phase progesterone levels were significantly lower in 10 and 7 cycles, respectively. Estradiol levels were also effected, particularly in the midcycle period. The clinical significance of these phenomena call for further confirmation in the frame of a large-scale study.
Keywords: Contraceptives, Oral, Hormonal; dospělí; Gonadotropins; Oral Contraceptives--side effects; Contraceptives, Oral; Hormones; Family Planning; Hungary; Research Methodology; kontraceptiva orální; Humans; abstinenční syndrom; kontraceptiva orální kombinovaná; Developed Countries; Contraceptive Agents; kontraceptiva orální hormonální; Endocrine System; Europe; Contraceptives, Oral, Combined; nitroděložní antikoncepční prostředky; Ovulation Suppression; Physiology; Follicle Stimulating Hormone; Estrogens; Clinical Research; progesteron; Contraceptive Methods--side effects; Contraceptive Agents, Female; Oral Contraceptives, Combined; gonadotropiny hypofyzární; Adult; Contraception; pohlavní steroidní hormony; Estradiol; Substance Withdrawal Syndrome; Intrauterine Devices; Progestational Hormones; ženské pohlaví; Gonadal Steroid Hormones; luteinizační hormon; lidé; Biology; Gonadotropins, Pituitary; estradiol; Progesterone; Eastern Europe; folikuly stimulující hormon; Contraceptive Mode Of Action; Luteinizing Hormone; Female